Behavioural Modernity dan Tipologi Akhlak Remaja Islam: Tinjauan Pendidikan Agama Islam dan Peranannya dalam Pembelajaran (SAP (Susunan Artikel Pendidikan), 2024)
The aim of this research is to find out the empirical assistance of the problems of PAI learning in the development of Islamic youth morals in global issues. This research uses descriptive qualitative research using the SLR (Systematic Literature Review) method. Then, the data collection technique consists of 1) data reduction; 2) Data Presentation and Analysis; 3) Drawing Conclusions. Based on the results of data collection, at least 19 research articles were found that were relevant in answering the 3 research questions (RQ) as follows: 1) RQ1. What are the Empirical Facts of Islamic Teenagers' Akhlaq?; 2) What is the influence of Behavioral Modernization on the Morals of Islamic Youth; 3) What is the Role of PAI as Learning in Islamic Youth Management? The results of the study show that there are three typologies of behavioral modernity towards the development of Islamic youth morals, namely 1) Demoralization; 2) Teacher Reorientation and Failure to Implement Ideal Learning Designs; 3) There is a Need for Innovation of Learning Instructional Design as the Role of PAI. Thus this research can be an empirical basis for the development of PAI learning in the future to be better and in accordance with the needs of students.